Association Between Pancreatitis and Immune-mediated Haemolytic Anaemia in Cats: A Cross-sectional Study. Issue 4 (May 2017) - Zoia, A.; Drigo, M.
Summary: In most cases, the underlying causes of feline pancreatitis and feline immune-mediated haemolytic anaemia (IMHA) remain unknown. Following the observation that some cats present with both diseases concurrently, the aim of this cross-sectional study was to investigate if the two disorders were associated statistically in this species. A residency case log of all cases seen at the Small Animal Hospital, University of Glasgow, Glasgow, UK, between July 2004 and December 2007, was used as the database for this study and an association between these two disorders was assessed by Fisher's exact test. Of the 155 sick cats included in the study, nine were diagnosed at the time of presentation with pancreatitis (prevalence of 5.8%) and 11 with IMHA (prevalence of 7.1%). In three of these cats both conditions were present concurrently at the time of presentation (prevalence of 1.9%). A significant association between these two disease was found (Odds Risk 8.63, exact 95% confidence interval 1.15–49.31, P = 0.0178). Two possible biological explanations for the statistical association found between these two diseases are that one of these conditions may represent the cause for the onset of the other or that an underlying disorder of the immune system may concurrently target feline red blood cells and the exocrine pancreas.